2019
DOI: 10.1371/journal.pone.0209992
|View full text |Cite
|
Sign up to set email alerts
|

Capacity adiposity indices to identify metabolic syndrome in subjects with intermediate cardiovascular risk (MARK study)

Abstract: BackgroundObesity increases mortality, and is linked to cardiovascular diseases and metabolic syndrome (MetS). Therefore, the purpose of this study was to analyze the ability of different adiposity indices to identify subjects with MetS among people with intermediate cariovascular risk.Materials and methodsThe cross-sectional study involved 2478 subjects, recruited by the MARK study. Adiposity measures: general adiposity by body mass index (BMI), central adiposity by waist-to-height ratio (WHtR), fat mass perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
25
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 46 publications
11
25
1
2
Order By: Relevance
“…WHR, and WHtR) was significantly better than the others in identifying most of these disorders. Similarly, in studies conducted in the Spanish (Caucasian) population, all obesity indices, except for the ABSI, had similar discriminatory power in the prediction of MetS [34]. When both sexes were analyzed separately, the BMI had the largest AUC in men and the WHtR and BRI had the largest AUCs in women.…”
Section: Plos Onementioning
confidence: 64%
“…WHR, and WHtR) was significantly better than the others in identifying most of these disorders. Similarly, in studies conducted in the Spanish (Caucasian) population, all obesity indices, except for the ABSI, had similar discriminatory power in the prediction of MetS [34]. When both sexes were analyzed separately, the BMI had the largest AUC in men and the WHtR and BRI had the largest AUCs in women.…”
Section: Plos Onementioning
confidence: 64%
“…Following these criteria, there is great disagreement in the classification (weighted kappa index values of CUN-BAE vs. BMI and WC of 0.068 and 0.174). In this way, other authors have reported that the obesity prevalences determined by BMI and %BF showed great differences [4,18,29].…”
Section: Discussionmentioning
confidence: 75%
“…This is an adiposity estimator based on BMI, sex, and age in Caucasian adults [13,14]. The CUN-BAE index was proposed as a better indicator of BF than BMI or WC in adults to predict cardiovascular disease and other outcomes, as well as, it might be better able to identify metabolically unhealthy individuals [15][16][17][18][19]. Therefore, the Spanish Society for the Study of Obesity (SEEDO) has promoted the use of CUN-BAE in strategies of obesity prevention since 2016 [11]; however, the evidence on the CUN-BAE is not convincing.…”
Section: Introductionmentioning
confidence: 99%
“…However, BRI is limited in predicting percentage of fat mass in elite athletes when compared with other commonly and readily available field methods such as bio‐impedance analysis or skinfold prediction models 63 . Several recent studies have shown that BRI could be used as an adipose indicator for determining the presence of eccentric left ventricular hypertrophy, 64 hyperuricaemia, 41,65 arterial stiffness, 66–69 CVD, 70,71 diabetes, 41,72–75 dyslipidaemia, 41,76–78 hypertension 41,79,80 and MetS 41–55 …”
Section: Discussionmentioning
confidence: 99%
“…BRI is a predictor of body fat percentage and visceral adiposity tissue, and its values range from 1 to 16 35 . Although studies have compared the prediction of MetS by BRI with traditional and novel anthropometric indices, 41–55 there is currently no meta‐analysis indicating whether BRI is a better predictor of MetS than BMI, WC, WHR, WHtR, ABSI or BAI. Therefore, this meta‐analysis aims to investigate whether BRI is superior to BMI WC, WHR, WHtR, ABSI or BAI in predicting MetS.…”
Section: Introductionmentioning
confidence: 99%